A plan to sustain the strategic plan for RC Agribusiness Center - Rallos, Elna M. eauthor; Rallos, Elna M.; Durana, Annalee D. (Davao City School of Management, University of the Philippines Mindanao, 2007)
RC Agribusiness Center, a producer of quality tissue culture plantlets and fresh fruit products, competes with multi-national banana producing firms. To effectively do so, it needs a strategic plan that will serve as the company's guide towards a sound human resource program and a better financial direction. An evaluation of the company's internal environment has identified a number of significant strengths and weaknesses. For strengths, the company has unique marketing in place, capacity in terms of volume of banana plantlets and fresh fruits, and the owner's will to operate despite unstable financial situation. The owner is also willing to improve the company's human resource department and encourage employee teamwork to help make the company survive. The company's weaknesses include the absence of an articulated set of corporate objectives, no proper budgeting methods, low yields due to low technology, unsound human resource practices, and operational problems. Likewise, from the evaluation of the company's external environment, it has identified various threats and opportunities. The company's opportunities include its lack of competition since it is the only locally established tissue culture laboratory in the entire Region XII. There is also increasing demand for banana tissue culture due to land expansion and rehabilitation for planting, support of government, awareness of banana planters to use the tissue cultured plantlets, and global campaign about the health benefits of banana. Among the company's threats are prevalence of pests and diseases, inadequate farm to market roads, peace and order concerns in Region XII, rapid expansion of multi-national banana plantation, price bargaining of new entrants that offers lower prices, and bargaining force of suppliers with cash on delivery terms and higher price. Combining the strengths, weaknesses, opportunities and threats in the light of the new formulated Vision, Mission, and Goals resulted in the identification of the three strategic proposals, namely: enhancing operational efficiency, fund allocation and market penetration. Enhancing operational efficiency will help the company answer the demand and supply of quality banana tissue culture and fresh fruit products. The strategy will also help the company to be a responsible employer to its strong asset, its employees. Fund allocation, on the other hand, will enable the company to allocate important needs for quality improvements and market penetration. Market penetration strategy will allow the firm to penetrate the banana industry not only in Region XII and Mindanao but also the entire Philippines. The identified strategies were all used to assure that RC Agribusiness Center can compete in the production of tissue cultured plantlets for the banana industry.
Thesis, Graduate (Master in Management)--University of the Philippines Mindanao, December 2007
Keywords: Strategic plan